Two different sequence elements within exon 4 are necessary for calcitonin-specific splicing of the human calcitonin/calcitonin gene-related peptide I pre-mRNA. - van Oers, C C (1994)
The calcitonin (CT)/calcitonin gene-related peptide I (CGRP-I) gene (CALC-I gene) is subject to alternative tissue-specific processing of its primary transcript. CT mRNA is the predominant mRNA produced in thyroid C cells, whereas CT gene-related peptide I mRNA is the main product in neurons of the central and peripheral nervous systems. The CT-specific exon 4 is surrounded by weak processing sites. In this study we have investigated whether exon 4 sequences are involved in the tissue-specific selection of the exon 4 splice acceptor site. The results indicate that two separate elements, termed A and B, in the 5' part of exon 4 are required for production of CT-specific RNA. These sequences are located between nucleotides 67 and 88 (A) and nucleotides 117 and 146 (B) relative to the 5' end of exon 4. Variation of the distance between these sequence elements and the 3' splice site of exon 4 does not change the processing choice. These sequence elements are functionally equivalent. CT-specific splicing requires the presence of both sequence A and B or duplicates of either sequence element in exon 4. The effect of these sequences on the RNA processing choice is overruled by mutation of the CT-specific uridine branch acceptor nucleotide into a commonly preferred adenosine residue.